Modelling the simultaneous calcination/sulfation behavior of limestone under circulating fluidized bed combustion conditions - Chen, Liang; Wang, Chunbo; Tong, Shuai; Anthony, Edward J. (Elsevier, 2019)
The simultaneous calcination/sulfation (SCS) reaction is the realistic reaction process for limestone use in CFB boilers. A SCS reaction model based on the randomly-overlapped pore concept, which takes into consideration the calcination of CaCO3, the sulfation of CaO and the sintering effect simultaneously, was developed. The results of this model fit well with the results from the thermogravimetric analyzer (TGA) tests and, thus this model was used to study the characteristics of the SCS reaction. The SCS reaction consists of a mass-loss stage and a mass-growth stage, and the two stages are seperated by a minimum mass point. The mass-loss stage is dominated by the calcination of CaCO3, while the mass-growth stage is dominated by the sulfation of CaO. The minimum mass point is a balance point of the mass change caused by the two reactions. The calcination reaction occurred in a layer of the particle. As the calcination reaction progresses, the reaction front moves inward and a CaO layer is formed. The SO2 in the calcination atmosphere can react with the CaO layer and produce CaSO4. The CaSO4 can fill the pores of the CaO layer and narrow the pore width, increase the CO2 diffusion resistance and consequently slow the calcination reaction. The sulfation reaction becomes slower as the reaction progresses. There was an upper limit to the sulfation conversion, which is much higher in the outer layer of the particle. For a typical particle with a radius of 200 μm, the sulfation reaction ceases in the inner part (0-150 μm) of the particle due to the exhaustion of SO2, while in the outer part of the particle (150-200 μm), the decrease of the sulfation rate is caused by the simultaneous decline of the reaction surface area, surface Ca2+ ion concentration and SO2 concentration.
Keywords: Limestone; Calcination; Sulfation; Random pore; CFB